RESPON MASYARAKAT TENTANG PASAR INUMAN DI DESA KAMPUNG BARU KOTO KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Khairin Nas; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Kampung Baru Koto Village, District of Inuman, Kuantan Singingi Regency. This research is titled "Community Response to Inuman Market in Kampung Baru Koto Village Inuman Sub-district Kuantan Singingi Regency in Riau Province". This study aims to determine the reason why the Inuman market has stopped growing and to determine the community’s opinion on the Inuman market. Sampling for this research is done by purposive sampling techniques. The total population of in 2015 amounted to 1,273 inhabitants with 331 heads of households. A sample of 30 people, representative of the population, was determined as the criteria. The method used is a quantitative method with a descriptive approach. The data filtering instruments used are observation, documentation and interview. The results of this research have generally been conducted by the researcher. The researcher can say that the cause of Inuman market not developing is the high prices of goods on the market; according to 26 respondents which is 87%. This is as a result of no large competition between traders. The public’s opinion to the Inuman market is low due to poor service in the market; according to 21 respondents which is 70%. Buyers are kings and queens who must be served well and if the service is not good then the buyers feel less comfortable.Keywords: response, community, market